Parental Social Comparison Related to Tutoring Anxiety, and Guided Approaches to Assisting Their Children's Home Online Learning During the COVID-19 Lockdown - Yang, Qiuyue; Gu, Jianjun; Hong, Jon-Chao (Frontiers in Psychology, 2021)
The COVID-19 pandemic has caused great disruption in education systems around the world. Schools have in some cases ended or limited on-site teaching, and have shifted toward home online teaching. This situation is likely to cause increased uncertainty and anxiety for parents who on one hand may question the quality of home online learning yet, on the other, may not feel sufficiently confident or competent to guide their children’s home online learning. Resulting anxiety is expected to be most evident in competitive educational contexts, such as those found throughout much of East Asia. Therefore, using China as the setting, and social comparison theory as the framework, this study examined how variation in parent social comparison relates to parent tutoring anxiety and, in turn, to the types of guided strategies parents use to promote their children’s home online learning. The results indicated a positive relationship between parental upward social comparison and parental tutoring anxiety, but a negative relationship between parent downward social comparison and parental anxiety. Parental tutoring anxiety is positively related to the confirmation and structure types, but negatively related to the discovery type of guided approaches. The implication of this study is that parents who resist tendencies of competitive upward social comparison are likely to adopt more effective approaches to guiding their children’s home online learning.